Older citizen participation in Portugal: an exploratory study of local initiatives - Ferreira de Almeida, Mariana (2016)
Participation has been gaining prominence in discussions of ageing, partly a result of the widespread notion of active ageing. The emphasis has not, however, been followed up by parallel advances in conceptualization and practice, and the term has lost specificity and meaning, particularly in connection with civic and political engagement of older citizens. How can senior citizen participation be defined? What kind of activities does it encompass? And what is being done in Portugal in this area? These are the questions the paper addresses, with data from an exploratory study on local “seniors’ participation” initiatives.